Electrochemical organization of monolayer protected gold nanoclusters on single-walled carbon nanotubes: significantly enhanced double layer capacitance - Mahima, Subhramanyam; Chaki, N. K.; Sharma, J.; Kakade, Bhalchandra A.; Pasricha, R.; Rao, A. M.; Vijayamohanan, K. (Journal of Nanoscience and Nanotechnology, 2006)
This paper reports a novel electrochemical route for anchoring monolayer protected gold nanoclusters (size 8 +/- 0.2 nm) on single-walled carbon nanotube bundles, resulting in the formation of hybrid materials. Monolayer protected gold nanoclusters prepared by modified Brust synthesis route were organized on SWNT bundles by cycling-the potential in dichloromethane between -1 to +1 V at a scan rate of 50 mV/s. Monolayer protected nanoclusters in electrolyte solutions possess ionic space charge around them (double layer charging), making them suitable for organization on nanotube bundles, by tuning the electrostatic interactions. More significantly, analysis of the double layer capacitance of these hybrid materials shows almost ten times increase in capacitance compared to that of bare SWNT bundles. We believe that these hybrid materials are potentially useful in nanoelectronics.
Keywords: double layer capacitance; double layer charging; hybrid materials; monolayer protected gold nanoclusters; single-walled carbon nanotubes

Eu3+ doped lanthanum oxide nanowhiskers: microwave hydrothermal synthesis, characterization and photoluminescence properties - Murugan, A. Vadivel; Viswanath, Annamraju Kasi; Kakade, Bhalchandra A.; Ravi, V.; Saaminathan, V. (Journal of Physics D-Applied Physics, 2006)
We report here a straightforward and rapid microwave - hydrothermal route providing an easy synthesis of Eu3+ doped La2O3 nanowhiskers. The nanostructured Eu3+ doped La2O3 is characterized by x-ray diffraction studies, scanning electron microscopy and photoluminescence (PL). The emission spectrum shows transitions from the excited 5D(0) state to F-7(J) (J = 0, 1, 2, 3, 4) levels of the Eu3+ ion. The most intense peak around 611 nm is due to the D-5(0) -> F-7(2) transition, expected from the Judd-Ofelt selection rules. PL spectra measurements demonstrate that the lanthanum oxide nanowhisker shows higher PL intensity.

Efficient route towards the covalent functionalization of single walled carbon nanotubes - Kakade, Bhalchandra A.; Pillai, Vijayamohanan K. (Applied Surface Science, 2008)
A simple and efficient method of chemical functionalization of both single and multiwalled carbon nanotubes has been discussed to give enhanced water solubility by rapidly and efficiently generating an appreciable amount of hydrophilic functional groups using microwave radiation. Surface functionalization containing more than 30 wt% of oxygen has been achieved, resulting into solubility of 2-5 mg/mL. Further covalent functionalization of such soluble SWNTs provides a remarkable degree of aniline functionalization through amidation, where the formation of polyaniline has been avoided. Functionalization of SWNTs is confirmed by techniques like electron microscopy, Fourier transform infrared spectroscopy, thermogravimetry, Raman spectroscopy, cyclic voltammetry and impedance spectroscopy. Electrochemical analysis suggests an enhanced double layer capacitance (similar to 110 F/g) of nanotubes after microwave treatment. Aniline functionalization of SWNTs shows possible variations on the nanotube topography with concomitant formation of a dynamic polymer layer on the nanotube surface. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Carbon nanotubes; Functionalization; Microwave; solubility

Electric field induced, superhydrophobic to superhydrophilic switching in multiwalled carbon nanotube papers - Kakade, Bhalchandra A.; Mehta, Rutvik; Durge, Apurva; Kulkarni, Sneha; Pillai, Vijayamohanan (Nano Letters, 2008)
Superhydrophobic multiwalled carbon nanotube bucky paper, fabricated after ozonolysis, shows fascinating electrowetting behavior, which could be remarkably tuned by changing key solution variables like the ionic strength, the nature of the electrolyte, and the pH of the water droplet. More significantly, the droplet behavior can be reversibly switched between superhydrophobic, Cassie-Baxter state to hydrophilic, Wenzel state by the application of an electric field, especially below a threshold value.

Enhanced field emission from hexagonal rhodium nanostructures - Sathe, Bhaskar R.; Kakade, Bhalchandra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Late, Dattatray J.; More, Mahendra A.; Joag, Dilip S. (Applied Physics Letters, 2008)
Shape selective synthesis of nanostructured Rh hexagons has been demonstrated with the help of a modified chemical vapor deposition using rhodium acetate. An ultralow threshold field of 0.72 V/mu m is observed to generate a field emission current density of 4 x 10(-3) mu A/cm(2). The high enhancement factor (9325) indicates that the origin of electron emission is from nanostructured features. The smaller size of emitting area, excellent current density, and stability over a period of more than 3 h are promising characteristics for the development of electron sources. (C) 2008 American Institute of Physics.